Hypoxia-induced Wnt/β-catenin signaling activation in subchondral bone osteoblasts leads to an osteoarthritis-like phenotype of chondrocytes in articular cartilage - Li, Fang; Tan, Qizhao; Li, Feng; Zhang, Ke; Liu, Zhongjun; Tian, Yun; Zhu, Tengjiao (Frontiers in Molecular Biosciences, 2023)
Background: Osteoarthritis (OA) is a whole-joint disease and characterized by alterations in the articular cartilage, subchondral bone, ligaments, and synovial membrane. The crosstalk between cartilage and subchondral bone plays a crucial role in the pathogenesis and progression of OA. Hypoxia has been reported to play an important role in cartilage degradation and subchondral bone remodeling in OA. In this study, we aimed to identify the involvement of hypoxia in modifying the osteoblast phenotypes and determine whether these alterations could influence the metabolism of chondrocytes. Methods: First, the levels of Hif-1α in subchondral bone of different compartments in patients with OA were assessed using immunohistochemistry (IHC). In in vitro, human primary osteoblasts were cultured under hypoxic and normoxic conditions, and the hypoxic or normoxic conditioned media (HCM and NCM) were used to culture human primary chondrocytes. Then, phenotypic changes in osteoblasts were assessed using reverse transcription-polymerase chain reaction (RT-PCR), Western blotting, and enzyme-linked immunosorbent assay (ELISA). Furthermore, the expression of type II collagen (COL2A1), aggrecan (ACAN), SRY-related high-mobility group-box gene 9 (SOX9), matrix metalloproteinase 13 (MMP13), and matrix metalloproteinase 3 (MMP3) in chondrocytes was measured using RT-PCR. Finally, the serum levels of Wnt-related proteins were determined using ELISA. Results: Hif-1α was significantly increased in severely sclerotic subchondral bone compared to less damaged subchondral bone. β-Catenin and SOST were identified as upregulated and downregulated in hypoxic osteoblasts, respectively. The hypoxia-induced results were confirmed by ELISA. Stimulating human primary chondrocytes with HCM significantly induced MMP13 and MMP3 and inhibited COL2A1, ACAN, and SOX9 mRNA expression. The serum levels of DKK-1 were significantly increased in human OA. Conclusion: Together, these findings revealed that hypoxia in subchondral bone is a key factor in the crosstalk between chondrocytes and osteoblasts and facilitates the shift of chondrocytes toward an OA-like phenotype probably by activating the Wnt/β-catenin signaling pathway in osteoblasts.